Therapeutic controversies over use of antioxidant supplements during cancer treatment: a scoping review - Woldeselassie, Mulugeta; Tamene, Aynadis (Frontiers in Nutrition, 2024)
Background: Antioxidant supplements are widely used during cancer treatment to prevent oxidative stress, reduce treatment toxicities, and improve patient outcomes. However, current literature reveals significant gaps suggesting that antioxidants may protect both healthy and tumor cells from oxidative damage, thereby reducing treatment efficacy. It is for this reason that antioxidant supplements have become a source of therapeutic controversy. Objective: To review therapeutic controversies over the use of antioxidant supplements during cancer treatment. Methods: Scoping review of the international published articles following the Arksey and O'Malley framework, cross-sectional studies, clinical and pre-clinical studies, systematic and umbrella reviews and grey literatures published from 2014 to 2024 with all age patient populations were included. A structured literature search was conducted of CINAHL, EMBASE, MEDLINE, Google Scholar, using key medical subject heading words and Cochrane Collaboration and Joanna Briggs Institute databases. All included studies were reviewed independently by two investigators. Data were extracted, collated by type of antioxidants, summarized in tables and synthesized for analysis. Result: A total of 1, 550 articles were identified. After reviewing all literatures, nineteen were full-text articles, grey literatures (2), and systematic reviews (42) and umbrella reviews (3), met the criteria for inclusion. In this review, the use of antioxidant supplements can benefit cancer cells in the same way as they do for normal cells during cancer treatment. In addition, not all antioxidants were effective in inhibiting oxidative stress, reduce treatment toxicities, and improve patient outcomes. Conclusion and recommendations: According to this review, the use of antioxidant supplements can benefit tumor cells in the same manner as they do for normal cells. Therefore, oncologists should advise not to take antioxidant supplements during chemotherapy and/or radiotherapy. Future research including potential clinical and preclinical trials, mechanistic studies, and exploration of different vitamin and mineral supplement studies are required to uncover the complete potential of antioxidant supplements for cancer treatment or determine their safety and effectiveness when used alongside standard cancer treatments. Furthermore, the results of this review could be used for future systematic review of therapeutic controversies over use of antioxidant supplements during cancer treatment.